Adaptasi Strategi Pemasaran Global Starbucks di Indonesia - Sabina Siti Sholeha; Nadya Fitriana; Theresia Longga (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
Starbucks Corporation, a global leader in the coffee industry, has successfully adapted its global marketing strategies to meet the needs of the Indonesian market. This study aims to analyze how Starbucks integrates product innovation, customer experience, technology utilization, strategic location selection, and loyalty programs to align with local preferences. Using a qualitative approach, this research examines the challenges and opportunities in adapting global strategies within Indonesia’s unique cultural and consumer landscape. The findings reveal that localization and cultural sensitivity are key drivers of Starbucks' success in Indonesia, enabling the company to maintain market leadership amidst increasing competition.